1980
DOI: 10.2527/jas1980.505945x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition of the Weaned Holstein Calf. II. Effect of Dietary Protein Level on Nitrogen Balance, Digestibility and Feed Intake

Abstract: Four cracked corn-based diets supplemented with 0, 5, 10 and 15% soybean meal (SBM) were fed to weaned male Holstein calves to study effects of protein level on digestibility and nitrogen balance, in one trial, and on feed intake, in another. Twelve calves were used in each trial in a replicated 4 x 4 Latin square design. Calves were 9 to 12 weeks of age at the start of the experiment and diets ranged from 9.9 to 16.2% crude protein (CP). In trial 1; feed intake was restricted to 80 g dry matter (DM) per kilog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
2

Year Published

1982
1982
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 10 publications
4
20
0
2
Order By: Relevance
“…Increasing the quantity of dietary CP supplied has also increased totaltract starch disappearance. Veira et al (1980) fed weaned Holstein calves high-concentrate diets with 0 to 15% soybean meal replacing cracked corn and showed that total-tract apparent starch disappearance increased linearly with increased dietary protein. Streeter and Mathis (1995) fed beef steers high-concentrate diets with fish meal supplemented to supply 0, 25, 50, and 75 g/d of additional N to represent 1.0to 1.5-fold of the steers' CP requirement.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the quantity of dietary CP supplied has also increased totaltract starch disappearance. Veira et al (1980) fed weaned Holstein calves high-concentrate diets with 0 to 15% soybean meal replacing cracked corn and showed that total-tract apparent starch disappearance increased linearly with increased dietary protein. Streeter and Mathis (1995) fed beef steers high-concentrate diets with fish meal supplemented to supply 0, 25, 50, and 75 g/d of additional N to represent 1.0to 1.5-fold of the steers' CP requirement.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies examined the responses of prepubertal ruminants to various dietary protein to energy ratios of different BW (Veira et al., ,b; Radcliff et al., ; Gabler and Heinrichs, ). These ratios used in these studies were mainly achieved by adjusting the concentration of CP with a similar amount of energy across the experimental diets.…”
Section: Discussionmentioning
confidence: 99%
“…For animals in the milk-fed group, all nutrition was derived from the milk or milk replacer and no additional feed was offered (either starter grain or hay). Ten published papers studied cattle receiving diets based on forage, concentrates, or a combination of forage and concentrates (weaned group) with 57 different dietary treatments, with animals ranging from 56 to 472 kg of BW (Whitelaw et al, 1961;Broster et al, 1963;Bowers et al, 1965;Bines and Balch, 1973;Stobo and Roy, 1973;Veira et al, 1980;Bagg et al, 1985;Hoffman et al, 2001;Gabler and Heinrichs, 2003;Marini and Van Amburgh, 2003).…”
Section: Methodsmentioning
confidence: 99%